اثر التدريب في تحسين الاداء الوظيفي في المؤسسة الاقتصادية - عواطف, عطاالله (University of eloued جامعة الوادي, 2020)
هدفت هذه الدراسة إلى التعرف على أثر التدريب في تحسين الأداء الوظيفي في المؤسسة الإقتصادية، حيث كان إسقاط الجانب التطبيقي على مؤسسة إتصالات الجزائر بالوادي، واعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي في جمع المعطيات والبيانات المتعلقة بالظاهرة، موضوع البحث، ولتحقيق هذا الهدف استخدمنا الإستبيان كأداة للدراسة وتم توزيع إستمارة الإستبيان داخل المؤسسة على عينة مقدارها 95 عامل، وقد اعتمدنا في تحليل البيانات على برنامج الحزمة الإحصائي ة للعلوم الإجتماعيةSPSS برنامج معالج الجداول Excelولاختبار الفرضيات اعتمدنا المتوسطات الحسابية، استخدام الإنحراف المعياري، اختبار تحليل التباين الاحادي (One Way Anova)كما تم استخدام أساليب الإنحدار والإرتباط لإثبات وجود علاقة بين متغيرات الدراسة، وفي الأخير خلصت الدراسة إلى ان التدريب عامل فعال في المؤسسة إذ يمثل الركيزة الأساسية في تطوير وتحسين أداء القوى العاملة.This study aimed to identify the impact of training on improving job performance in the economic institution, where the applied aspect was dropped on the Algeria Telecom Corporation in the valley, and we relied in this study on the descriptive analytical approach in collecting data and data related to the phenomenon, the subject of research, and to achieve this goal we used the questionnaire As a study tool, the questionnaire was distributed within the institution to a sample of 95 workers, and we relied on data analysis on the SPSS program, the Excel spreadsheet program, and to test the hypotheses, we adopted the arithmetic averages, the use of standard deviation, the One Way Anova test as well. Regression and correlation methods were used to prove the existence of a relationship between the study variables, and in the end, the study concluded that training is an effective factor in the organization as it represents the main pillar in developing and improving the performance of the workforce.
مذكرة ماستر ادارة اعمال
Keywords: التدريب، أساليب التدريب، الأداء، الأداء الوظيفي.: training, training methods, performance, job performance.